Indoor Air Quality and Its Impact on Stunting Risk in Children - Ra. Hoetary Tirta Amallia Amallia; Feliyanti; Rr. Rina Antasari; Nilawati (Poltekkes Kemenkes Surabaya, 2025)
Indoor air quality is an important factor that needs attention in everyday life because it has a significant impact on health, especially for children under 5 years who spend almost 90% of their time indoors. Pollutants that pollute indoor air can increase the risk of infection in children, which can stunt their growth and cause stunting. Indonesia is one of the countries with the highest prevalence of stunting. Therefore, this study aims to analyze indoor air quality which can be a risk factor for stunting. This research was cross-sectional research. The research results showed that the concentration of Volatile Organic Compounds (VoC), CO (Carbon Monoxide), CO2 (Carbon Dioxide), and the number of microbes in the air exceeded the quality standard values ​​permitted for the air where stunted children live. Meanwhile, for home air for children who are not stunted, it does not exceed the quality standard value. This shows that the air quality in the homes of children who are pregnant is in the bad category with high levels of pollutants present. The bad effects of these pollutants can result in recurring infectious diseases in children, which can cause children to become malnourished, which can ultimately lead to stunting. The results of statistical testing using the Independent Sample T-Test for each parameter show a p value of 0.005, which is smaller than alpha, meaning there is a significant difference between the air quality in the room where stunted and non-stunting children live. This means that there is a relationship between air quality and the incidence of stunting in children.